2008
DOI: 10.1038/eye.2008.113
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab and augmented trabeculectomy for neovascular glaucoma in young diabetic patients

Abstract: Controlling IOP due to NVG in young diabetic patients is difficult and augmented trabeculectomy has a very high failure rate. The addition of intravitreal bevacizumab in the management of NVG particularly in young diabetic patients may improve the success rate of IOP control. It is known that bevacizumab retards neovascularisation. It may also be modulating wound-healing response as well. Bevacizumab may have a potential role in the surgical management of NVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 13 publications
(15 reference statements)
0
22
0
3
Order By: Relevance
“…20 This problem is particularly intense in young patients. 21 Significantly raised levels of VEGF have been demonstrated in patients with rubeosis and NVG as well as other This study showed that complete regression of INV after IVB and PRP occurred in 14 eyes (82.4%). In 3 patients (17.6%), INV was reduced but did not disappear completely.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…20 This problem is particularly intense in young patients. 21 Significantly raised levels of VEGF have been demonstrated in patients with rubeosis and NVG as well as other This study showed that complete regression of INV after IVB and PRP occurred in 14 eyes (82.4%). In 3 patients (17.6%), INV was reduced but did not disappear completely.…”
Section: Discussionmentioning
confidence: 86%
“…The addition of IVB in the management of NVG particularly in young diabetic patients may improve the success rate of IOP control. 21 In conclusion, trabeculectomy with intraoperative MMC after an adjunctive treatment with IVB and PRP is a good treatment modality in the management of eyes with NVG. It is effective in reducing NVI and intraoperative complications during trabeculectomy.…”
Section: Discussionmentioning
confidence: 98%
“…2,3 Dramatic regression of iris or angle neovascularization after intracameral or ivBe injection has been reported. [5][6][7][19][20][21] Recent larger cases series and prospective design reports have revealed its effi cacy and safety. 13,[22][23][24][25] Ehlers and associates revealed that ivBe/PRP treatment resulted in more rapid decrease in IOP and regression of neovascularization than PRP alone in NVG.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have looked at intracameral, intravitreal, and subconjunctival administration. [29][30][31][32][33] Pre placed sutures and intra-operative Sodium hyaluronate can be used avoid sudden decompression as this might lead to intraoperative bleeding. The use of releasable sutures and laser suturolysis post-operatively can help titrate IOP in early post-operative period.…”
Section: Trabeculectomymentioning
confidence: 99%